ASSESSING LEADERSHIP INTERJECTIONS IN NIGERIA’S TURBULENT POLITICAL ECONOMY. (Journal of the Management Sciences, 2024)
This paper examines leadership decisions/indecisions taken in a bid to solving burgeoning problems occasioned in Nigeria political economy. It assesses the attributes and styles of leaders as it is brought to bear on decision making in a turbulent politico-economy milieu. The paper use qualitative design where data was only obtained from secondary sources including books, journals and internet materials. The paper discovered failure of leadership in assessing and correcting counter-productive decisions taken in turbulent periods. Thus, the paper recommends assessment and correction in decisions or policies by leadership as they bring their managerial attributes to bear on their democratic style.
Keywords: Leadership, interjections, turbulences, political economy, Nigeria.